AGAINST ALL ODDS (PERGESERAN STANDAR KECANTIKAN DALAM IKLAN KORPORAT â€œREAL BEAUTYâ€ DOVE) - Emyliani, Tania; Krisdinanto, Nanang; Akhsaniyah, Akhsaniyah (LONTAR: Jurnal Ilmu Komunikasi, 2019)
This study looked at how the matching of signs related to the shift in standard of beauty incorporate advertising "Real Beauty" with Dove's wish image. In seeing this suitability, the author usesthe Semiotics method by Charles Sander Peirce to reveal the sign by grouping it into icons, indices, andsymbols found in corporate advertising. The shift related to beauty standards will be seen in thecorporate advertisements "Real Beauty, Meet Kylee" as the global version and "Real Beauty: Friends" asthe local version (Indonesia). The use of these two advertisements also aims to see whether Dove isconsistent in carrying out the "Real Beauty" campaign. The results of the sign analysis show that theglobal version of the advertisement reflects a shift in the standard of beauty (a new definition of beauty),the feminist movement, gender bias resistance and against social construction. Meanwhile, the signanalysis on the local version of the ad is still fixated on traditional beauty standards, gender bias,patriarchal culture, and the social construction that makes the ad "Real Beauty: Friends" does not reflectthe company's wish image and fails to maintain consistency in campaigning. Dove's failure to maintainthe consistency of the "Real Beauty" campaign with wish image can make Dove experience an identitycrisis that leads to a bad reputation or image for the company, such as the failure of the company's wishimage formation, and failure to reach marketing targets such as Dove expected.